Pengaruh Brand Trust, Harga dan Promosi Terhadap Keputusan Pembelian Kartu Telkomsel bagi Mahasiswa Fakultas Ekonomi UKI Toraja - Widianto Widianto; Helba Rundupadang; Jens Batara Marewa (CV. Ulil Albab Corp, 2024)
The aim of the research is to determine the simultaneous influence of Brand Trust, price and promotion on the decision to purchase Telkomsel cards for UKI Toraja economics faculty students. The type of research used in this research is quantitative research. The results of the research are (1) Brand Trust influences purchasing decisions. (2) Price influences purchasing decisions. And (3) Promotions influence purchasing decisions